The contemporary Islamic art in Malaysia: the PSKK styles (1985-2009) / Sallehuddin Mohamed, Mumtaz Moktar and D'zul Haimi Md Zain - Mohamed, Sallehuddin; Moktar, Mumtaz; Md Zain, D'zul Haimi (Universiti Teknologi MARA, 2018)
The establishment of the National Islamic Calligraphy Art Association in 1985 also known as Persatuan Seni Khat Kebangsaan (PSKK) was to bring back the usage of the Islamic calligraphy and educate the general public the correct method of writing according to the order of the classical Islamic calligraphy. It also has contributed styles in contemporary of Islamic art in Malaysia. Four basic components of PSKK styles compose of idea, tools, form and content which are inter-related. The styles and content manifested by the PSKK artists were well received by the general public. It is undeniable to state that the PSKK's contributions to the development of Contemporary Islamic Art in Malaysia is of utmost importance. It reflects the identity of Malaysia forms and meaning in Islamic culture as a whole.